Demonstration of lymphoid antigens in decalcified bone marrow trephines. Issue 8 (August 1987) - Hall, P A; Lindeman, R; Butler, M G; Amess, J A; D'Ardenne, A J
Abstract : A panel of antibodies recognising lymphoid and epithelial antigens in formalin fixed, paraffin embedded sections was applied to a series of 54 bone marrow trephines decalcified by formic or edetic acids. Normal trephines and cases infiltrated by myeloid, lymphoid, and epithelial tumours were included. Patterns of reactivity were distinct and allowed the different diseases to be distinguished. All lymphoid tumours expressed leucocyte common antigen, with B cell tumours staining with MB1 and MB2, and T cell tumours staining with MT1 and UCHL1. T cell acute lymphoblastic leukaemia (ALL)/lymphoblastic lymphoma all stained with MT1, but some were negative with UCHL1. B cell ALL/lymphoblastic lymphoma also stained with MT1, but could be distinguished by its reactivity with MB1 and MB2. Reed-Sternberg cells did not stain with any reagent. Normal and neoplastic myeloid cells stained with MT1. Carcinomas stained with CAM 5.2 but were negative for lymphoid markers except MB2 staining in some cases. A case of neuroblastoma could be distinguished from ALL/lymphoblastic lymphoma by its lack of reactivity with all antileucocyte antibodies and its staining with antineurone specific enolase. Although not ideal, if used together, this panel of reagents may usefully be applied to routinely fixed and processed, decalcified bone marrow trephines.